Hugh MacDiarmid as inspirer of the “Scottish Literary Renaissance” - Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Lemeshchenko-Lagoda, Viktoriia (Видавничий будинок ММД, 2012)
С. M. Grieve, best known under his pseudonym Hugh MacDiarmid, is сredited with effecting a Scottish literary revolution which restored an indigenous Scots literature and has been acknowledged as the greatest poet that his country has produced since Robert Bums. When Hugh MacDiarmid began writing in the 1920s, it was precisely the sense of a new dispensation, an urgent need to write Scotland into the new century dial motivated him and many of his contemporaries - in music, painting, sculpture and literary and cultural criticism. This was the period MacDiarmid named “The Scottish Literary Renaissance”.
Keywords: Scottish literary; Renaissance; Scots dialects; MacDiarmid; English language